Pengembangan Aplikasi Asisten Virtual Menggunakan Machine Learning Berbasis Mobile untuk Meningkatkan Pelayanan Kampus di Universitas Muhammadiyah Bangka Belitung: Pengembangan Aplikasi Asisten Virtual Menggunakan Machine Learning Berbasis Mobile untuk Meningkatkan Layanan Kampus di Universitas Muhammadiyah Bangka Belitung - Ari Gunawan; Eka Altiarika; Suprayuandi Pratama; Yudistira Bagus Pratama (Universitas Muhammadiyah Bangka Belitung, 2024)
The development of technology, particularly in the fields of artificial intelligence (AI) and machine learning, has transformed the paradigm of information services across various sectors, including education. This research aims to develop a mobile-based virtual assistant application using machine learning algorithms to enhance information accessibility at Universitas Muhammadiyah Bangka Belitung. The research methodology employed in this study is a qualitative approach with a waterfall development model. Data collection was conducted through observation, interviews, and questionnaire distribution. The research findings indicate that the developed virtual assistant application is capable of providing faster, more precise, and accurate information services to students, faculty, and other campus stakeholders. The benefits of this research include improved time efficiency in information services, reduction of errors in information delivery, and enhancement of campus reputation. This research has practical implications, including recommendations for Universitas Muhammadiyah Bangka Belitung to continue developing and implementing virtual assistant applications as part of a strategy to enhance technology-based information services in the future. This research's theoretical contributions expand the literature on the application of AI and machine learning technologies in higher education contexts in Indonesia, while also providing practical insights for other educational institutions interested in adopting similar technologies. Furthermore, this research opens up opportunities for further studies into the development of AI-based information systems in educational environments. Keywords: Virtual Assistant; Machine Learning; Artificial Intelligence; Mobile Application; Information Services